(untitled) (Journal of the College of Basic Education, 2026)
Technological advancements in all areas of physical education, particularly in teaching methods and wrestling, have led to the adoption of educational models. The use of the ADEAI model with learners will play a significant role in facilitating the educational process in wrestling lessons. The researcher employed the experimental method due to its suitability to the problem, the hypotheses, and the prepared research units. The experimental method is considered one of the best and most appropriate methods because it allows for direct and accurate observation, making it the most efficient means of acquiring knowledge. The sample was taken from fourth-year students in the Department of Physical Education and Sports Sciences at the College of Basic Education, Al-Mustansiriya University, using the purposive method during the 2025-2026 academic year. The researcher concluded that the educational units based on the ADEAI model in the experimental group resulted in improved speed and balance grip strength in freestyle wrestling. Furthermore, the speed-strength exercises included in the educational units contributed to an improvement in the students’ performance level.